A nők teológiai képzésének első száz éve Kolozsváron - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The First Hundred Years of Women’s Theological Education in Cluj-Napoca The initial topic of the study at hand addresses the beginnings. In terms of women’s education, one of the positive effects of the Reformation is the insistence on the widespread availability of the Bible, which was inevitably followed by the eradication of illiteracy among women. Following the Reformation, another argument emerged in favour of the importance of educating women in theology: society regarded women as a key role in raising children, so in order to raise their children educated in theology, their ability to do so became a priority. The second topic addresses the direct preconditions of the theological education of women, especially the changes in the 19th-century school history, which resulted in women’s admission to universities and opening up the opportunity for them to obtain degrees in higher education. Furthermore, the study presents the past hundred years of women’s education in theology in the Protestant educational centres of Cluj-Napoca – from the first enrolment, the first ordained woman minister up to the present time.